The value of cooperativism in the Colombian post-conflict - Alfonso Cabrera, Lizandro (DIXI, 2021)
Theme and scope: Demonstrate the value and role of cooperativism as an alternative to true peace. Methodology: An initial sweep is carried out regarding the real state of the peace process, the progress of the agreements signed in Colombia and the impact that cooperativism may have on this process. Características: The union is the way to keep the hope of peace. FINDINGS: The cooperative is the way to make visible that Colombia that wants to progress from the province. Conclusiones: Cooperativism, understood as the possibility of associating, of joining efforts and dreams in an organized and communal way, becomes a tool so that those people who really have the decision to change their lives and get ahead can contribute to this reconstruction of the national country.There are many ways that cooperativism supports successful experiences and minimal chances of failure. Well, the only, the first and the best way that man had, has and will have to generate revolutions, understood as change is the union of forces.
Keywords: peace; agreement; post-conflict; cooperativism